Ethnobotanical study and conservation strategy of medicinal plants in the ecotourism area of Kedah Rainforest Lodges in Aceh, Indonesia - RIDWAN RIDWAN; MA'RIFATIN ZAHRAH; RAHMAWATY RAHMAWATY (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ridwan, Zahrah M, Rahmawaty. 2022. Ethnobotanical study and conservation strategy of medicinal plants in the ecotourism area of Kedah Rainforest Lodges in Aceh, Indonesia. Biodiversitas 23: 6227-6237. Medicinal plants have long been used by indigenous communities, including Gayo people in Aceh, Indonesia. The conservation and sustainable utilization of medicinal plants can be integrated with ecotourism activities. Kedah Rainforest Lodges is an ecotourism area in the Protected Forest area of Forest Management Unit (FMU) Region V Aceh, Indonesia, which is an important source of medicinal plants, clean water and nature tourism. However, biodiversity in the area is threatened by excessive human activity, including the long-standing tradition of Gayo people using medicinal plants. Therefore, this study aimed to investigate medicinal plants used by the local community living around Kedah Rainforest Lodges using an ethnobotanical approach and to identify a strategy for the conservation of medicinal plants using strengths, weaknesses, opportunities and threats (SWOT) analysis. A combination of field observations, interviews, documentation and focus group discussions were employed for data collection. The result of the ethnobotanical study identified 44 species belonging to 31 families of medicinal plants used by Gayo people in the studied area. Asteraceae is the family with the largest number of medicinal plant species, while herbs are the most common habitus of the medicinal plants and leaves are the most used plant part. Based on SWOT analysis, there are several strategies to conserve medicinal plants in Kedah Rainforest Lodges, including (i) the rehabilitation of degraded areas through the enrichment of medicinal plants to create living pharmacies; (i) the development of facilities to support medicinal plants ecotourism; and (iii) partnerships with related stakeholders to obtain funding and enhance the capacity of the area manager and staff.